Stakeholders and the composition of the voting rights of the board of directors - Galai, Dan; Wiener, Zvi (Journal of Corporate Finance, 2008)
We propose a new approach to dynamic representation of different groups of stakeholders on the board of directors. This approach is based on a simple economic model of the firm, with an objective function to maximize its market value. We look at the marginal claim of each stakeholder on the assets of the firm. It divides the voting rights based on the change in value of each stakeholder with a one dollar change in the value of the firm as a whole. We translate these conditions to relative voting powers on the board. While there are many claims in the academic and popular literature on sharing voting rights on the board, our paper is the first to propose a quantitative dynamic model of the power sharing in the corporation.